UTOPIAS DO FALSO COLORIDO: COMENTÁRIOS SOBRE LITERATURA CONTEMPORÂNEA - da Bernardes, Erick (LINKSCIENCEPLACE, 2026)
This article seeks to discuss the "romantic" vision that has the Brazilian Communicator while professional. Will be examined the relationship between art and the market today and their intellectual perspective vis-à-vis the globalization. In addition to scoring some aspects of the critic Graciliano Ramos critic on contemporary bias to bring out its positioning about the writer and his craft.